Apristurus breviventralis, a new species of deep-water catshark (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) from the Gulf of Aden - Kawauchi, Junro; Weigmann, Simon; Nakaya, Kazuhiro (Zootaxa, 2014)
A new deep-water catshark of the genus Apristurus Garman, 1913 is described based on nine specimens from the Gulf of Aden in the northwestern Indian Ocean. Apristurus breviventralis sp. nov. belongs to the ‘brunneus group’ of the genus and is characterized by having pectoral-fin tips reaching beyond the midpoint between the paired fin bases, a much shorter pectoral-pelvic space than the anal-fin base, a low and long-based anal fin, and a first dorsal fin located behind pelvic-fin insertion. The new species most closely resembles the western Atlantic species Apristurus canutus, but is distinguishable in having greater nostril length than internarial width and longer claspers in adult males. Apristurus breviventralis sp. nov. represents the sixth species of Apristurus from the western Indian Ocean and the 38th species globally.